PENGARUH PPN, PPNBM, DAN PEMERIKSAAN PAJAK TERHADAP PENERIMAAN PAJAK YANG TERDAPAT DI KPP PRATAMA DEPOK CIMANGGIS - Indra Wadi; Mhd Ali Akbar (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
This study aims to determine the effect of Value Added Tax (PPN), Sales Tax on Luxury Goods (PPNBM), and Tax Audit on Tax Revenue. This research was conducted at KPP Pratama Depok Cimanggis. The population in this study was 16,648 corporate taxpayers. This research uses quantitative methods; the sample is calculated using the Slovin formula and found 99 corporate taxpayers. Data was collected through questionnaires and analyzed using the SPSS Version 26 program with the data quality test method, classical assumption test, multiple linear regression analysis, t-test, and F test. Based on the study, it was concluded that, partially, Sales Tax on Luxury Goods (PPNBM) does not affect Tax Revenue, while Value Added Tax (VAT) and Tax Audit affect Tax Revenue. Meanwhile, Value Added Tax (PPN), Sales Tax on Luxury Goods (PPNBM), and Tax Audit affect Tax Revenue.